Risk Of Sharia Banking In Indonesia: Viewed From Types Of Financing - Mashilal, Mashilal (AL-ARBAH: Journal of Islamic Finance and Banking, 2020)
AbstractPurpose - This study aims to analyze the influence of macroeconomic variables and specific variables of the bank on sharia bank credit risk in Indonesia based on the type of financing agreement. Islamic bank credit risks based on financing agreements consist of credit risk based on profit sharing, receivables and rent.Method - This study uses secondary time series data. The data used is the data of Sharia Commercial Banks in Indonesia from January 2015 to March 2019. The data analysis method uses Vector Autoregression (VAR) with Eviews 10 software tools.Result - Based on the results of the impulse response, the impact of shock on macroeconomic variables and banking-specific variables on sharia bank credit risk in general is almost the same except for credit risk based on rent in certain variables. Judging from the variance decomposition, in general the CAR variable has the greatest influence on the risk of Islamic bank credit in Indonesia.Implication - There must be an acceleration in strengthening the capital structure of Islamic banks in Indonesia.Originality- This research fills in the blanks about syariah bank credit risk based on the type of financing agreement.Â